Human Leucocyte Antigen G and Murine Qa-2 Are Critical for Myeloid Derived Suppressor Cell Expansion and Activation and for Successful Pregnancy Outcome - Dietz, Stefanie; Schwarz, Julian; Velic, Ana; González-Menéndez, Irene; Quintanilla-Martinez, Leticia; Casadei, Nicolas; Marmé, Alexander; Poets, Christian F.; Gille, Christian; Köstlin-Gille, Natascha (Frontiers in Immunology, 2022)
During pregnancy, maternal immune system has to balance tightly between protection against pathogens and tolerance towards a semi-allogeneic organism. Dysfunction of this immune adaptation can lead to severe complications such as pregnancy loss, preeclampsia or fetal growth restriction. In the present study we analyzed the impact of the murine MHC class Ib molecule Qa-2 on pregnancy outcome in vivo. We demonstrate that lack of Qa-2 led to intrauterine growth restriction and increased abortion rates especially in late pregnancy accompanied by a disturbed trophoblast invasion and altered spiral artery remodeling as well as protein aggregation in trophoblast cells indicating a preeclampsia-like phenotype. Furthermore, lack of Qa-2 caused imbalanced immunological adaptation to pregnancy with altered immune cell and especially T-cell homeostasis, reduced Treg numbers and decreased accumulation and functional activation of myeloid-derived suppressor cells. Lastly, we show that application of sHLA-G reduced abortion rates in Qa-2 deficient mice by inducing MDSC. Our results highlight the importance of an interaction between HLA-G and MDSC for pregnancy success and the therapeutic potential of HLA-G for treatment of immunological pregnancy complications.